2022
DOI: 10.1186/s12885-022-09316-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor treatment and healthcare consumption near death in the era of novel treatment options for patients with melanoma brain metastases

Abstract: Background Effective systemic treatments have revolutionized the management of patients with metastatic melanoma, including those with brain metastases. The extent to which these treatments influence disease trajectories close to death is unknown. Therefore, this study aimed to gain insight into provided treatments and healthcare consumption during the last 3 months of life in patients with melanoma brain metastases. Methods Retrospective, single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…This is probably because the side effects of targeted therapy are in general less severe compared to the side effects of immune therapy. Also, targeted therapy induces faster response and therefore also serves a palliative purpose in terms of quality of life preservation 12,13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably because the side effects of targeted therapy are in general less severe compared to the side effects of immune therapy. Also, targeted therapy induces faster response and therefore also serves a palliative purpose in terms of quality of life preservation 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…12 We found that only 28 out of 89 patients started with a first (new) line of targeted therapy within 30 days prior to death, which is less than a previous study in which most BRAF-positive patients received targeted therapy during the last months of life. 13 However, those were patients with brain metastases only and the study also included therapy that started prior to the last 3 months of life.…”
Section: Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some caveats remain concerning the excessive drug use in terminal-stage melanoma due to high expectations for their efficacy and tolerability. 1 , 2 , 3 , 4 , 5 The present study compared the use of anticancer agents in terminal-stage melanoma before and after the introduction of novel agents and identified factors associated with making decisions at the end of life (EOL), especially focused on the final 30 days of life. 1 , 2 , 3 , 4 …”
mentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 The present study compared the use of anticancer agents in terminal-stage melanoma before and after the introduction of novel agents and identified factors associated with making decisions at the end of life (EOL), especially focused on the final 30 days of life. 1 , 2 , 3 , 4 …”
mentioning
confidence: 99%